A universal artificial diet for corn rootworm (Diabrotica spp.) larval biopesticide assays - Ho, Khanh-Van; Hibbard, Bruce E.; Do, Thu T. H.; Pekarcik, Adrian J.; Huynh, Man P. (Frontiers in Insect Science, 2024)
We identified a single diet formulation that can be used for three Diabrotica species including southern (SCR), western (WCR), and northern corn rootworm (NCR) by evaluating the performance of these pests on specialized diets (F9800B diet for SCR, WCRMO-2 diet for WCR, and NCRMO-1 diet for NCR) and a larval diet (F9772 diet) widely used for lepidopteran species. After 10 days of rearing, the WCRMO-2 diet yielded better or equal larval growth and development of all three rootworm species compared to other diets. For SCR larvae, the WCRMO-2 diet outperformed other diets. Larval fresh weight, percent molt to 2nd instar, and percent molt to 3rd instar on the WCRMO-2 diet were 12-fold, 2.7-fold, and 14-fold increases, respectively compared to that of the F9800B diet. Significantly more SCR larvae survived on the WCRMO-2 diet (98.9%) than on the F9800B diet (90.6%). The WCRMO-2 diet supported WCR and NCR larvae equal to the NCRMO-1 diet and better than other diets. The F9772 diet was the worst diet of all examined species. The availability of a universal diet (the WCRMO-2 diet) for the three Diabrotica species would facilitate research programs to monitor resistance development and develop new control tactics targeting these important pests.